2012
DOI: 10.1177/0959651812453668
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of fractional-order unstable delay systems by fractional-order controllers

Abstract: In the present paper stabilization of a class of fractional-order unstable delay systems by fractional-order controllers is investigated. To derive the sufficient conditions for stability, an analysis based on the Nyquist stability criterion has been adopted. The analysis is carried out with fractional-order [proportional–integral] and [proportional–derivative] controllers to obtain the upper bound for the time delay. Furthermore, the paper proposes the conditions on the parameters of the controllers which mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Due to 0 < < 1, sgn[ sgn( )] = sgn( ). The reaching dynamics governed by (25) will create a stronger push from both sides of the switching manifold [22]. According to the above analysis, a fractional-order switching law can be proposed and defined as…”
Section: Fractional-order Nonsingular Fast Terminal Sliding Mode Contmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to 0 < < 1, sgn[ sgn( )] = sgn( ). The reaching dynamics governed by (25) will create a stronger push from both sides of the switching manifold [22]. According to the above analysis, a fractional-order switching law can be proposed and defined as…”
Section: Fractional-order Nonsingular Fast Terminal Sliding Mode Contmentioning
confidence: 99%
“…Meanwhile, sliding mode control is an efficient approach in the application of linear or nonlinear control. For the foregoing reasons, there are more and more new control methods composed of fractional calculus and sliding mode control [22,23], and their application fields have been gradually expanded from integerorder dynamic systems to fractional-order ones [24][25][26]. Besides, compared with traditional integer-order control, fractional-order control can offer more degrees of freedom to designers to meet a predefined set of performance criteria [27].…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, fractional calculus has been extensively used in a variety of fields of physics and engineering applications, for example, dynamical systems, 2 viscoelastic damping, 3 signal processing, 4 diffusion wave, 5 biomedical applications, 6 stochastic systems, 7 and chaotic systems. [8][9][10] Recently, many fractional order controllers are developed like fractional order proportional integral derivative (FOPID) control, 11,12 fractional order proportional integral (PI) and proportional differential (PD) control, 13,14 fractional order lead-lag control, 15,16 fractional CRONE controller, 17 fractional order model reference adaptive control, 18,19 and sliding mode control of fractional order systems. 20 In most of the applications, the controllers are of proportional integral derivative (PID) type due to its simplicity and appropriate performance in a variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…A novel design method of a FOPID for fractional order with time delay systems is given by Boudjehem [14]. In other studies, the FOPID controllers has been suggested for fractional order unstable time delay systems [15], [16]. Moreover, stability analysis was also carried out in these studies.…”
Section: Introductionmentioning
confidence: 99%